Jump test can detect changes in power during training in junior BMX riders - Bosse, C.; Beeloo, D. C. M.; Castelijns, L. C. E.; De Ruiter, C. J.; Van Den Wildenberg, R. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: The purpose of this study was to detect indicators of neuromuscular fatigue which may predict overtraining is important, as the ability to monitor acute changes in performance could help in the prevention of overtraining. As several studies have shown, jump tests can detect neuromuscular fatigue (Andersson et al., 2008; Ronglan et al., 2006). Methods: Eight male BMX riders of the national junior selection performed three countermovement jumps (CMJ) and drop jumps (DJ) twice weekly for twelve weeks using a Ballistic Measurement System. To reduce the amount of data, only CMJ and performance variable peak power were incorporated in the analysis. On each testing day, athletes completed Profile of Mood States questionnaire (POMS). POMS energy index, the ratio of vigor to fatigue, was calculated. After each training session, data of training load (RPE) were collected. Bivariate correlations between peak power and POMS and RPE scores were conducted for each athlete. Paired samples t-tests compared data at different times during measurements. Results: Peak power increased (2-25%) for seven out of eight subjects. Subject 8 showed a decrease in peak power (19%) and POMS energy index (69%); he turned out to be injured. POMS energy index was highly variable; however, there was a significant increase from week 1 to week 12 (t=-2.46;p<0.05). For three relative unloading weeks, training load was respectively 69%, 48% and 39% compared with the other weeks. There was a significant increase in energy index between before and after the first unloading week (t=-2.24;p<0.05), but not for the other unloading weeks. Discussion: Performance on the CMJ and DJ was constant, suggesting that only functional overreaching (FO) occurred; FO enables athletes to fully recover with only short-term performance decrements (Kuipers, 1998; Nederhof et al., 2006). Large variances in POMS scores indicate that healthy athletes are able to cope with fluctuations in mood. The jump test was sensitive enough to detect changes in performance over time and may serve as a potential measure of fitness in athletes. However, it cannot be concluded that changes in subjective variables were related to changes in performance, since only few significant relations were found. In additional research, the present study may serve as a baseline and performance can be related to this baseline.